Ion‐Implant Isolated Vertical GaN p‐n Diodes Fabricated with Epitaxial Lift‐Off From GaN Substrates (Phys. Status Solidi A 4∕2019). Issue 4 (19th February 2019) - Wang, Jingshan; McCarthy, Robert; Youtsey, Chris; Reddy, Rekha; Xie, Jinqiao; Beam, Edward; Guido, Louis; Cao, Lina; Fay, Patrick
Abstract : Ion‐Implant Isolation Vertical GaN p‐n diodes fabricated using band‐gap selective photoelectrochemical wet epitaxial lift‐off processing enables homoepitaxial growth for low‐defect‐density devices. Nearly identical performance to control devices on GaN substrates and no indication of material quality degradation is found. This technique provides a possible route to achieve flexible thin‐film power electronics with high performance and low cost. More details can be found in article number1800652 by Jingshan Wang, Patrick Fay, and co‐workers.